2006
DOI: 10.1002/cne.20961
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of neurons expressing parvalbumin in the human amygdala

Abstract: Amygdalar intrinsic inhibitory networks comprise several subpopulations of γ-aminobutyric acidergic neurons, each characterized by distinct morphological features and clusters of functionally relevant neurochemical markers. In rodents, the calcium-binding proteins parvalbumin (PVB) and calbindin D28k (CB) are coexpressed in large subpopulations of amygdalar interneurons. PVBimmunoreactive (-IR) neurons have also been shown to be ensheathed by perineuronal nets (PNN), extracellular matrix envelopes believed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
55
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 83 publications
(139 reference statements)
6
55
0
Order By: Relevance
“…Perineuronal nets showed evident hollow, mesh-like appearance and neuron-like shape (Fig 1A&B). Their morphological features suggests preferential association with large multipolar neurons, confirming previous reports in human and nonhuman primate amygdala (Hartig, et al, 1995,Pantazopoulos, et al, 2006. WFA intracellular labeling was not detected in cells with typical neuronal morphology.…”
Section: Wfa Labeling In Human Blc-cosupporting
confidence: 90%
See 4 more Smart Citations
“…Perineuronal nets showed evident hollow, mesh-like appearance and neuron-like shape (Fig 1A&B). Their morphological features suggests preferential association with large multipolar neurons, confirming previous reports in human and nonhuman primate amygdala (Hartig, et al, 1995,Pantazopoulos, et al, 2006. WFA intracellular labeling was not detected in cells with typical neuronal morphology.…”
Section: Wfa Labeling In Human Blc-cosupporting
confidence: 90%
“…Only few nets were detected in the ABN (18,096 ± 21,208) and CO (15,496 ± 8,348). As reported previously (Pantazopoulos, et al, 2006), and shown as an example in Fig. 2, perineuronal nets tend to cluster along the lateral portion of the LN, and in the magnocellular BN region.…”
supporting
confidence: 84%
See 3 more Smart Citations